Literature Review Picture of Mental Revolution to Improve Citizenship Characteristics, Especially Among Generation Z - Renita Wildy Hernanda; Ane Rahma Sapitri; Khofifah Al Adawiyah; Riska Amalia; Dwi Iman Muthaqin (Publikasi Indonesia, 2021)
The character development of citizens, especially among the Z generation is something that must be considered. In psychology, the characteristics of Generation Z can be compared to the characteristics of adolescents and the transition to early adulthood. The increase in the character of Generation Z can be influenced by psychological conditions that can be pursued through the application of character education. Character development education is a process that is always ongoing and will never end. To create the characteristics of citizens who make good citizens (good citizenship), it can be done through the mental revolution movement. The method used in this study is a literature review related to the mental revolution and the characteristics of citizens, especially among Generation Z. The results of this study state that improving the characteristics is very necessary related to improving the welfare of the country and supporting the progress of the country during increasingly competitive global competition. . The mental revolution movement is an effort to improve the character education of citizens, through the cultivation of multicultural values.